The specific needs of doctors with mental health problems: qualitative analysis of doctor-patients' experiences with the Practitioner Health Programme. (4th March 2017) - Brooks, Samantha K.; Gerada, Clare; Chalder, Trudie
Abstract: Objectives : The current paper aimed to explore doctor-patients' views about their treatment from the Practitioner Health Programme (PHP), a UK-based service treating health professionals with mental health/addiction problems. Aims were to gain insights into the issues most important to patients and consider whether a service specifically for doctors is important in helping to overcome barriers to accessing mental healthcare. Methods : Nine doctor-patients attending PHP took part in semi-structured interviews between September 2010 and June 2011. Thematic analysis was used to explore recurring patterns in the data. 134 written comments from PHP patients were also included. Results : Participants reported difficulties in finding appropriate treatment; problems were often severe by the time PHP was involved. Concerns about confidentiality, judgement and impact on career were obstacles to help-seeking and important issues during treatment. Analysis of written comments provided further support for these findings. Conclusion : Whilst some of the needs of mentally unwell doctors mirror the needs of patients in general – e.g. a supportive and non-judgemental attitude from clinicians – they do have specific needs related to confidentiality and stigma.